2011
DOI: 10.1002/ceat.201100206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brønsted and Lewis Acidities on Catalytic Activity of Heteropolyacids in Transesterification and Esterification Reactions

Abstract: PW) were prepared and used as acid catalysts for transesterification and esterification reactions. These catalysts have double acidity properties, i.e., Lewis acidity and Brønsted acidity, that are suitable for the conversion of waste cooking oil into biodiesel. The highest efficiency was 59.2 % and 94.7 % corresponding to transesterification and esterification reactions by Ti 0.6 H 0.6 PW with moderate Lewis acidity. The relationship between the acidic properties and the catalytic activity is discussed in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Some researchers attempted to solve this issue by introducing Lewis acids into the resins [20][21][22][23]. Magnotta and Gates [20] reported that the acidic property of the complex formed by AlCl 3 -sulfonic acid can be similar to that of the superacid solution of SbF 5 + FSO 3 H. Shi et al [23] showed that the efficiency of acid-catalyzed transesterification and esterification reactions depend on the subtle balance between Lewis and Brønsted acidities. It has been proved that the coordination of a Lewis acid with a Brønsted acid can increase its original acidity [24].…”
Section: Introductionmentioning
confidence: 98%
“…Some researchers attempted to solve this issue by introducing Lewis acids into the resins [20][21][22][23]. Magnotta and Gates [20] reported that the acidic property of the complex formed by AlCl 3 -sulfonic acid can be similar to that of the superacid solution of SbF 5 + FSO 3 H. Shi et al [23] showed that the efficiency of acid-catalyzed transesterification and esterification reactions depend on the subtle balance between Lewis and Brønsted acidities. It has been proved that the coordination of a Lewis acid with a Brønsted acid can increase its original acidity [24].…”
Section: Introductionmentioning
confidence: 98%
“…In terms of both atomic economy and green synthesis, heterogeneous solid state acid catalysts that work actively with easily separation for recyclability are highly desirable. The acid value of 0.61 mmol·g −1 for IFMC-200 was detected by titration with aqueous ammonia, which is smaller than those of ZnCl 2 (7.96 mmol·g −1 ) and Keggin structure Zn 1.2 H 0.6 PW 12 O 40 (1.14 mmol·g −1 )30, but higher than those of other Lewis solid state acid catalysts (e.g., Y-zeolites, 0.54 mmol H + ·g −1 )57. In this regard, IFMC-200 was evaluated as a heterogeneous catalyst in the esterification of fatty acids with a series of alcohols (Figure 4).…”
Section: Discussionmentioning
confidence: 73%
“…POM-based materials with Lewis and Brønsted acidity and reversible redox activity have been utilized as efficient solid acid and electron transfer catalysts for the production of industrially important chemicals since the late 1970s232425262728. Recently, POM-based materials were also used as acid catalysts for biodiesel production29303132. In most cases, Lewis acidic POM-based catalysts could be obtained through the following strategies: (i) exchanging protons with Lewis acidic cations, including Zn II , Al III , Sn IV , Fe III and so on32, (ii) incorporation of rare earth metal ions into the vacant sites of POM ions3334, and (iii) supporting POMs on Lewis acidic porous materials, for instance, Ta 2 O 5 and zeolites313536.…”
mentioning
confidence: 99%
“…Hence, the acidic sites in those mesopores become unavailable at time of the reaction and hence, at higher Keggin densities (>0.5 nm −2 ) or TPA loadings, higher than 45 wt.% showed reduced catalytic activity. From the trend followed by the B/L curve, it can be said that an optimal level of Lewis acid and Bronsted acid site influences the transesterification reaction positively …”
Section: Resultsmentioning
confidence: 99%